Lamina cribrosa thickness correlated with posterior scleral thickness and axial length in monkeys - Jonas, Jost B. (Acta ophthalmologica, 2016)
Purpose To explore associations of lamina cribrosa thickness with axial length and thickness of the posterior sclera in monkeys. Methods Examining histological sections by light microscopy, we measured the thickness of the lamina cribrosa and posterior sclera and axial length. Results The study included 28 animals (28 eyes) with a mean age of 13.3 ± 4.9 years (range: 3-24 years) and mean axial length of 18.9 ± 1.4 mm (range: 17-21 mm) (22 eyes after experimental temporary central retinal artery occlusion; four eyes after a permanent occlusion of the posterior ciliary artery; and two eyes without any intervention). Mean thickness of the lamina cribrosa was 167 ± 30 μm (range: 115-273 μm). Thinner lamina cribrosa thickness was significantly associated with longer axial length (standardized correlation coefficient beta: -0.42; p = 0.026), with thinner sclera at the posterior pole (beta: 0.56; p = 0.002) and with thinner sclera at the disc border (beta: 0.55; p = 0.002). Lamina cribrosa thickness was not significantly related to temporary central retinal artery occlusion (p = 0.14) or to permanent posterior ciliary artery occlusion (p = 0.49) or age (p = 0.46). Conclusions As in humans, lamina cribrosa thickness in non-glaucomatous monkeys got thinner with longer axial length and with thinner posterior sclera. These data may be of interest for studies on the process of emmetropization/myopization in monkeys, and they may be of interest for the studies on the biomechanics of the optic nerve head.